Some taxonomic notes on the Caradrina (Eremodrina) filipjevi (Boursin, 1936) species group (Lepidoptera, Noctuidae) - Volynkin, Anton V.; Matov, Alexey Yu.; Chen, Liusheng (Zootaxa, 2016)
Caradrina Ochsenheimer, 1816 is a large xylenine genus restricted to Holarctic and Ethiopian regions. The full revision of the genus has been published by Hacker (2004). The genus subdivided into eight subgenera: Caradrina, Platyperigea Smith, 1894, Boursinidrina Hacker, 2004, Kalchbergiana Hacker, 2004, Eremodrina Boursin 1937, Levantrina Hacker, 2004, Weigertrina Hacker, 2004 and Paradrina Boursin 1937, and contains 156 described species (Hacker 2004; Hacker & Legrain 2006; Fibiger & Hacker 2007).